2023
DOI: 10.1186/s40364-023-00467-8
|View full text |Cite
|
Sign up to set email alerts
|

Functions and mechanisms of lncRNA MALAT1 in cancer chemotherapy resistance

Abstract: Chemotherapy is one of the most important treatments for cancer therapy. However, chemotherapy resistance is a big challenge in cancer treatment. Due to chemotherapy resistance, drugs become less effective or no longer effective at all. In recent years, long non-coding RNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) has been found to be associated with the development of chemotherapy resistance, suggesting that MALAT1 may be an important target to overcome chemotherapy resistance. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 95 publications
0
13
0
Order By: Relevance
“…MALAT1 is mostly overexpressed in human cancers and its expression is associated with tumor size and stage as well as patients' poor survival (103). MALAT1 has been recently identified as an important RNA which enhances cellular resistance to chemotherapy (104).…”
Section: Common Cernas In the Axesmentioning
confidence: 99%
“…MALAT1 is mostly overexpressed in human cancers and its expression is associated with tumor size and stage as well as patients' poor survival (103). MALAT1 has been recently identified as an important RNA which enhances cellular resistance to chemotherapy (104).…”
Section: Common Cernas In the Axesmentioning
confidence: 99%
“…Moreover, the interaction of MALAT1 with the nuclear protein hnRNP C has been shown to support the translocation of MALAT1 from the nucleus to the cytoplasm, promoting the transition from the G2 to the M phase [57]. On the other hand, many studies have indicated the role of MALAT1 in the resistance of cancer cells to chemotherapy in chronic myeloid leukemia, head and neck squamous cell carcinoma, and hepatocellular carcinoma [58], increasing the ability to repair DNA, evade cell cycle checkpoints, and regulate apoptosis, autophagy, and stemness of cancer cells. Moreover, MALAT1 stimulates the cell cycle of liver cells.…”
Section: Malat1 In Cell Cycle Regulationmentioning
confidence: 99%
“…Moreover, knockdown of MALAT1 induced the process of apoptosis and cell cycle arrest in the replication phase in human umbilical vein endothelial cells (HUVECs) [71]. Increased MALAT1 expression was demonstrated in acute myeloid leukemia (AML) and chronic myeloid leukemia (CML), and knockout of MALAT1 in AML was found to inhibit proliferation by arresting the cell cycle in the G0/G1 phase and promote apoptosis of cancer cells by increasing the expression of caspase-3, -8, and -9 proteins [58,72].…”
Section: Diseases Related To the Malat1 Genementioning
confidence: 99%
“…MALAT1 has been suggested as a potential indicator for the diagnosis and prognosis of cancer. [5][6][7][8][9][10] The epidermal growth factor receptor (EGFR) is a cellular protein that facilitates cell growth. A mutation in the gene for EGFR can make it grow too much, which can cause cancer.…”
Section: Introductionmentioning
confidence: 99%